Risky teenager behavior in a vocational high school - Suci Musvita Ayu; Marsiana Wibowo; Liena Sofiana (Institute of Advanced Engineering and Science, 2019)
Adolescence is a very complex period. Various teen problems haunt when they grow up to become adults. The same teenagers successfully face the challenges of their development so that they are free from a variety of risky behaviors. However, some of them also smoke, consume alcohol, have free sex, commit violence, and use drugs. This research is a qualitative study with a phenomenological approach in which researchers explore and try some risky behaviors in health and factors that influence and how adolescents in vocational high schools end up committing some risky behavior. The results of the study show that teens who do not have risky behavior and who do have some risk behaviors have different understandings related to the impact of these behaviors. People around teenagers influence how teenagers will behave. These influential people can cause teenagers to take risky behavior, such as family problems, get bad examples from parents, family members, peers, and idols. Factors that influence adolescents to end up committing risky behavior are the understanding of the negative effects of risk behavior. The various causes of influential people include parents, peers, religious leaders, idols, perceived benefits, self-control, and intention. The internal and external factors of adolescents determine whether the teenager will do or not risky behavior. Strong collaboration between internal and external factors shapes behavior which is not risky in adolescents, and vice versa.